Influence of kenaf and coir fibers in problematic soil for road works - Abdul Jalil, Falil Nisa (2019)
Pavement construction on natural subgrade is most concern nowadays due to the variation of subgrade soil. The properties of existing subgrade soil play the important role in producing the best condition of road especially in rural area. The usual approach in solving weak soil is by remove and replaces the existing soil with any stronger materials, which is expensive. One of the economical ways to improve the soil properties is soil reinforcement using natural fibers. Use of natural fibers is advantageous due to their availability, cost effectiveness, favourable strength and environmental friendliness. This research was developed to study the influence of coir fiber and kenaf fiber in problematic soil in terms of road work purposes. First, the geotechnical properties of soil were studied to classify the soil type. Natural fibers were prepared in two conditions which are untreated sample and treated with 5% sodium hydroxide (NaOH) sample before mixing with soil. To confirm the alteration of morphology of the fibers, scanning electron microscope (SEM) test was performed. Furthermore, the mechanical properties of natural fiber-soil mixture were assessed. Direct shear test, consolidation test and California Bearing Ratio (CBR) test were carried out on original soil, untreated fiber- soil, and treated fiber-soil. The results revealed that the tensile strength of both fibers was increased after being treated with sodium hydroxide. The inclusion of untreated and treated fibers into soil has increased the optimum moisture content (OMC) and decreased the maximum dry density (MDD). The rate of consolidation for reinforced soil increased and resulting in lower value of rate of volume compressibility. The strength of soil was increased up to 48% when reinforced with untreated coir fiber. For soil reinforced kenaf fiber, the strength increased 29.6% with untreated kenaf fiber and 35.5% with treated kenaf fiber. The results of CBR values for unsoaked and soaked condition were increases as the inclusion of fibers for all mixed samples. According to Arahan Teknik Jalan 5/85, the minimum requirement of CBR value for subgrade layer is 5% and all samples of soil reinforced coir fiber and kenaf fiber, achieve the minimum value. Overall, the properties of soil used have been identified and classified as organic clay with high plasticity. The inclusion of coir fiber and kenaf fiber improved the geotechnical properties of soil in terms of settlement behavior and shear strength. Natural fibers increased the CBR values up to 109% in unsoaked condition. In conclusion, all objectives have been satisfied and it can be said that natural fiber had influenced the properties of soil in terms of its shear strength, settlement and CBR values.